Selenophene-containing heterotriacenes by a C–Se coupling/cyclization reaction - Schwartz, Pierre-Olivier; Förtsch, Sebastian; Vogt, Astrid; Mena-Osteritz, Elena; Bäuerle, Peter (Beilstein Journal of Organic Chemistry, 2019)
A new novel family of tricyclic sulfur and/or selenium-containing heterotriacenes 2–4 with an increasing number of selenium (Se) atoms is presented. The heterotriacene derivatives were synthesized in multistep synthetic routes and the crucial cyclization steps to the stable and soluble fused systems were achieved by copper-catalyzed C–S and C–Se coupling/cyclization reactions. Structures and packing motifs in the solid state were elucidated by single crystal X-ray analysis and XRD powder measurements. Comparison of the optoelectronic properties provides interesting structure–property relationships and gives valuable insights into the role of heteroatoms within the series of the heterotriacenes. Electrooxidative polymerization led to the corresponding poly(heterotriacene)s P2–P4.
Keywords: conducting polymer; C–S coupling; C–Se coupling; heteroacene; selenophene